How initial price history influences expectation formation in multi-asset experimental markets: An exploratory case study - Kresta Aleš; Sedláková Michaela (Economics and Business Review, 2025)
We present an exploratory study on expectation formation in a controlled experimental setting. Participants predicted the prices of three risky assets, with their key information being the initial price history. Our research investigates the impact of the initial price history on overall price dynamics and the participants’ coordination. We provide tentative evidence highlighting several key points. Firstly, a stable initial price history reduces asset price volatility. Secondly, the correlation between assets during the initial price history is crucial for price dynamics. Notably, two assets exhibited strong negative dependence, which significantly influenced participants’ expectations. It is important to note that this dependence persisted in subsequent price evolution. In general, the initial price history played a pivotal role in shaping participants’ expectations. Given the exploratory nature of this study, we acknowledge that these findings are preliminary and should be interpreted with caution. We also point to ways for future research to validate our initial findings.